Associação entre o funcionamento executivo, atividade física, e aptidão física e aeróbia em idosos saudáveis - Luís Miguel Guedes Marques (2018)
The main objective of this cross-sectional study is to understand how physical activity, aerobic and functional fitness can modulate cognitive function, namely executive functioning. Sample was comprised by 32 older adults (12 males and 20 females; mean age = 68,8 yrs.) aged between 61 and 77 years old and the following variables were evaluated: 1) Executive functioning, namely processing speed, verbal fluency, working memory and mental flexibility; 2) Cardiorespiratory fitness (VO2max by Bruce protocol) and 3) levels of physical activity (7 days MTI accelerometer). The results showed: i) significant differences (p = 0.000) on VO2max between gender; however, no other differences were observed in any other variables; ii) VO2max correlated with global physical fitness and with different verbal fluency and processing speed neurocognitive tests; iii) a positive significant relationship between was observed between executive functioning and the variable VO2máx; iii) no significant differences were found between executive functioning with SFT, MVPA and sedentary behavior. The present study suggests, therefore, that a better aerobic capacity, which seems to be different between elderly men and women, is positively associated with a bettre executive functioning.